Effects of Single-Task Versus Dual-Task Training on Balance Performance in Older Adults: A Double-Blind, Randomized Controlled Trial - Patima Silsupadol (2018)
Silsupadol P, Shumway-Cook A, Lugade V, van Donkelaar P, Chou LS, Mayr U, Woollacott MH. Effects of single-task versus dual-task training on balance performance in older adults: a double-blind, randomized controlled trial. Objective: To compare the effect of 3 different approaches to balance training on dual-task balance performance in older adults with balance impairment. Design: A double-blind, randomized controlled trial. Setting: University research laboratory. Participants: Older adults (N=23) with balance impairment (mean age, 74.8y). They scored 52 or less on the Berg Balance Scale (BBS) and/or walked with a self-selected gait speed of 1.1m/s or less. Interventions: Participants were randomly assigned to 1 of 3 interventions: single-task training, dual-task training with fixed-priority instructions, and dual-task training with variable-priority instructions. Participants received 45-minute individualized training sessions, 3 times a week for 4 weeks. Main Outcome Measures: Gait speed under single-task and dual-task conditions was obtained at baseline, the second week, the end of training, and the twelfth week after the end of training. Other measures, including the BBS and the Activities-specific Balance Confidence (ABC) Scale, were collected at baseline and after training. Results: Participants in all groups improved on the BBS (P<.001; effect size [ES]=.72), and walked significantly faster after training (P=.02; ES=.27). When a cognitive task was added, however, only participants who received dual-task training with fixed-priority instructions and dual-task training with variable-priority instructions exhibited significant improvements in gait speed (P<.001, ES=.57; and P<.001, ES=.46, respectively). In addition, only the dual-task training with variable-priority instructions group demonstrated a dual-task training effect at the second week of training and maintained the training effect at the 12-week follow-up. Only the single-task training group showed a significant increase on the ABC after training (P<.001; ES=.61). Conclusions: Dual-task training is effective in improving gait speed under dual-task conditions in elderly participants with balance impairment. Training balance under single-task conditions may not generalize to balance control during dual-task contexts. Explicit instruction regarding attentional focus is an important factor contributing to the rate of learning and the retention of the dual-task training effect. © 2009 American Congress of Rehabilitation Medicine.